Hubungan Komunikasi Terapeutik Guru Bimbingan Konseling dengan Self-Disclosure Siswa - Alfazunta, Ajib; Setiana, Wiryo; Lukman, Dede (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
The healing technique known as Therapeutic Communication is usually carried out by counseling guidance (BK) teachers. A person's ability to disclose information about oneself to others (Self-Disclosure) is a person's tendency to get a sense of comfort. The purpose of this research is to find out about the relationship between the therapeutic communication of guidance counseling teachers (BK) and self-disclosure in students. The method used in this study is the method of correlational quantitative research (correlation research). The results of this study indicate that therapeutic communication with self-disclosure has a relationship as evidenced by a significance value of 0.036 <0.05 and the value of the correlation number (Pearson correlation) obtained is 0.254 or 26%. Evidenced by the BK teacher showing concern and showing acceptance to students to trigger student self-disclosure.